The Social Security Systems in Belarus, The Republic of Kyrgyzstan and Kazakhstan in Perspective of the Aging Population - Iwański , Rafał; Jaskuła, Paweł; Rataj, Zuzanna (Studia Oeconomica Posnaniensia, 2019)
This paper is a well-detailed comparative study of the reforms and changes that have come into existence in the social policies in Belarus, The Republic of Kyrgyzstan and Kazakhstan since the collapse of the USSR. Presenting numbers and statistics essentially concentrate on the phenomenon of the aging populations in the analysed countries. The principal purpose of this investigation is the presentation of the diversity of social security systems (with a particular emphasis on pension schemes) which emerged in the chosen post-soviet republics after their gaining independence after 1991. The research encompasses a specific comparison of several variables: the unique approach of the described countries regarding the calculation of current and future pensions, the structure of budget social expenditures in the last decade and their demographic forecast until 2050. Our distinctive study of pension schemes exposes a very different range of potential threats associated with the correct functioning of currently existing social security systems in the investigated cases. The reason is the significant increase in the number of pensioners (those people above 65 years old) there. The models based on the solidarity pension scheme will only be able to be retained in the countries with a positive population growth trend.